Problemy własności innych, poza gruntowymi, wkładów w rolniczych spółdzielniach produkcyjnych: [Property issues and other non-land contributions to agricultural and production cooperatives] (Studia Prawnicze / The Legal Studies, 1963)
In contrast to land contributions which constitute the main source of land for cooperatives, other contributions are less important for equipping cooperatives with the required production tools. Outbuildings, small machines and tools, livestock owned by members of the agricultural production cooperative can only be used in a large farm to a relatively small extent.The law establishes the name “other contributions” for all contributions that may be made by members, with the exception of the land contributions. The subject of these contributions may be in particular:• parts of agricultural land contributed by a member as a land contribution and a household plot that is not subject to contribution, that is, buildings and household facilities firmly associated with the land, for example, ameliorative, milling and pond facilities, wells, silos, etc.;• movables or personal property, that is, agricultural live and dead stock, buildings and implements necessary for the operation of processing enterprises and consumer services enterprises;• things designated only by genus and kind, that is, feed, seeds and, by agreement, some live and dead stock;• money.According to the author, the law takes into account both the needs of cooperatives in the means of production depending on the type and scope of their economic activity and the low suitability of the available means of production for the collective farm. In fact, the law gives freedom to the Charters of cooperatives not only in determining the scope of the obligations to make contributions as it is practised for land contributions, but even in the establishment of this obligations.Art. 108 of the law on cooperatives and their unions stating that the Charter may specify the type and amount of live and dead stock that members can keep for their personal use is essential for determining which of available means a member may be required to contribute. Although the law allows for an optional interpretation of this issue, we should accept a certain decision on it to be mentioned in the Charter. Because members should not engage in such branches of production in their own households as the cooperative does in an amount exceeding the satisfaction of their personal and their family’s needs which cannot be satisfied by the collective farm. Therefore, members may personally use only those means of production that are necessary for production permitted by the Charter.Thus, members may be required to contribute to the cooperative the means of production that they have had at the time of joining the cooperative in excess of the rate permitted by the Charter or have acquired during their membership by inheriting, giving or purchasing.Members may be obliged to contribute to the cooperative the available means of production: both those of which they own and those of which they use based on the right of ownership.This article also considers the issue of the nature and extent of the rights of cooperatives regarding contributions, the rights of members to make contributions and the procedure for the return of contributions in case of a termination of membership.